English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2 answers

Minor error in the question: it should be "prove that det(A) = 0 or det(A) = 1". If det(A) = -1 A is definitely not idempotent!

det(AB) = det(A).det(B)
So det(A^2) = (det(A))^2.

If A is idempotent, A^2 = A. So det(A) = det(A)^2.
=> det(A) [det(A) - 1] = 0
=> det(A) = 0 or 1.

2006-12-20 20:02:56 · answer #1 · answered by Scarlet Manuka 7 · 2 0

A is idempotent if A^2 = A
=> det (A^2)= det(A)
=> det(A) ^2 = det( A)
=> det(A) (det(A) -1) =0
=> det(A) =0 or det(A)-1 =0
so det(A)=0 or det(A) =1.

your statement is not quite correct! .

2006-12-21 12:33:41 · answer #2 · answered by Anonymous · 2 0

fedest.com, questions and answers